Crédit Agricole: rejection of attempt to (further) delay publication of Commission cartel decision. (22nd February 2019) - Ferro, Miguel Sousa
Abstract: Case T-419/18R Crédit Agricole v Commission, 25 October 2018, EU:T:2018:726 One more challenge to the publication of a Commission infringement decision is rejected by the GCEU, in the provisional measures stage, based on absence of fumus boni juris . But the delay effect is achieved. Successive appeals based on the repetition of an argument repeatedly rejected by the Court raises concerns about the balance of conflicting interests.